Hubungan Lama Duduk dan Berdiri dengan Nyeri Low Back Pain pada Perawat : The Association between Duration of Sitting and Standing and Low Back Pain among Nurses - Silvi Hilyatul Auliya; Feri Catur Yuliani; Dwi Puji Susanti (Universitas Ngudi Waluyo, 2026)
Nurses are a vital part of the healthcare system with a significant responsibility in providing nursing care. Heavy and repetitive physical activities, such as lifting patients and working in a sitting or standing position for extended periods can increase the risk of musculoskeletal disorders, particularly low back pain (LBP). This study aimed to analyze the relationship between sitting and standing duration and the incidence of LBP among nurses at Pati Islamic Hospital based on age, gender, length of service, work unit, and work shift. This quantitative study used a cross-sectional design. The samples were 51 nurses which selected through purposive sampling. Data were obtained using a structured questionnaire and analyzed using the Chi-Square test. The majority of respondents were aged 25–35 years (39.2%), female (70.6%), had 5–10 years of service (49%), worked in inpatient units (58.8%), and worked on day shifts (51%). The most frequent sitting time was 2–4 hours (49%), and standing time was <2 hours (43.14%). The most common complaints of low back pain were mild (52.94%) and moderate (47.06%) pain. A chi-square test showed a significant association between sitting duration (p=0.014) and standing duration (p=0.029) with LBP. There is a significant association between sitting and standing duration and low back pain in nurses. Static working positions pose risks, necessitating ergonomic interventions and workload management